Intensive outpatient treatment of PTSD and complicated grief in suicide-bereaved military widows. Issue 2 (7th February 2022) - Ohye, Bonnie; Moore, Cynthia; Charney, Meredith; Laifer, Lauren M.; Blackburn, Allyson M.; Bui, Eric; Simon, Naomi M.
Abstract: We report on a novel 2-week intensive outpatient treatment program (IOP) for 24 widows bereaved by the suicide death of their veteran spouse. We targeted symptoms of posttraumatic stress disorder (PTSD) and complicated grief (CG) concurrently in three separate cohorts. All patients either witnessed the death or discovered the body of their deceased partner, who was a veteran of the United States military. PTSD, CG, and depression symptom severity decreased significantly from pre- to post-treatment, with effect sizes of 0.85, 1.21, and 1.35, respectively. These outcomes provide preliminary support for an IOP to treat co-occurring PTSD and CG among widowed survivors of veteran suicide.